The effect of short radiation treatment breaks on chemo‐radiotherapy for oropharyngeal cancers. Issue 12 (29th September 2021) - Rybkin, Alisa; Kang, Jung Julie; Lee, Anna; Kitpanit, Sarin; Fan, Ming; Mohamed, Nader; Cartano, Olivia; Zakeri, Kaveh; Gelblum, Daphna; Sherman, Eric; Dunn, Lara; Boyle, Jay; et al.
Abstract: Background: Numerous studies and guidelines suggest an outcome detriment from radiation treatment breaks (rTBs) and the need for compensatory dosing in patients with head and neck cancer. Methods: In a consecutive cohort of 521 patients with oropharyngeal squamous cell carcinoma (OPSCC), we investigated the impact of rTBs and prolongation of overall treatment time (OTT) on OS, DFS, LRC, and cancer recurrence using competing risk and multivariate analyses. Results: Neither OTT prolongation by ≤2 days nor rTBs of ≤3 days were associated with detriments to clinical outcomes. Consecutive breaks of ≥3 days were also not significantly associated with detriment to clinical outcomes. There was significantly increased competing mortality in those with longer breaks. Conclusions: In OPSCC patients treated with definitive concurrent chemoradiotherapy, there is no significant association between disease failure and total rTBs of ≤3 consecutive or scattered days. Further investigation is needed for longer breaks.